IMPLEMENTASI PRINSIP CEPAT, SEDERHANA DAN BIAYA RINGAN DALAM PENYELESAIAN SENGKETA HUBUNGAN INDUSTRIAL DI INDONESIA - Maswandi Maswandi (Universitas Medan Area, 2016)
The genesis of law No. 2 of 2004 Concerning Industrial Relations DisputeSettlement can not be separated from the Indonesian government’s efforts to meet theaspirations of people who crave the industrial relations dispute settlement to avoidprotracted and can be completed as simple as possible and at a low cost. Aspirations ofthe people is of course not independent due during the industrial relations disputesettlement through Law No. 22 of 1957 on the Settlement of Labour Dispute take quitsome time until many years and involve many agencies and require no small cost, so thatthe judicial settlement of disputes with the principle of last, simple and low cost as desiredLaw 48 of 2009 instead of Law No. 4 of 2004 on Judicial Power has not done well.